Pengembangan Media Pembelajaran Teknik Lanjutan Pencak Silat Berbasis Aplikasi Martial Art Augmented Reality Book - nelson, sonya (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
Augmented reality technology is a technology that can impact various fields, including education. This research aims to create pencak silat learning materials that are practical, interesting and valuable. The research development model uses Borg and Gall, including data collection, planning, development, design validation, design evaluation, product testing, product evaluation, product testing, use, product evaluation and mass production. Based on expert validation, the development of martial arts learning materials based on augmented reality technology provides very good results and is feasible to use. The average expert validation result is 86,53%. Student response to the use of this media in learning pencak silat is very good with the acquisition of scores in the small group test of 87,32% and in the large group test of 89,08%.